Pioneering molecularly-level Fe sites immobilized on graphene quantum dots as a key activity descriptor in achieving highly efficient oxygen evolution reaction - Rinawati, Mia; Chang, Ling-Yu; Chang, Chia-Yu; Chang, Ching-Cheng; Kurniawan, Darwin; Chiang, Wei-Hung; Su, Wei-Nien; Yuliarto, Brian; Huang, Wei-Hsiang; Yeh, Min-Hsin (Chemical engineering journal (Lausanne, Switzerland : 1996), 2024)
[Display omitted] •A precisely engineered molecular Fe site were proposed, –a breakthrough in the catalysis design.•The molecularly well-defined Fe sites were successfully immobilized onto the GQDs matrix.•The pioneering strategy of molecular Fe immobilization on the OER kinetic intricacies were explored.•The well dispersed molecular Fe sites on the GQDs matrices demonstrated not only an outstanding OER features, but also stability. The emergence of efficient electrocatalysts to facilitate the thermodynamically demanding and kinetically challenging oxygen evolution process (OER), which includes the coordinated transfer of four protons and four electrons, remains an issue. The effective transfer of energy encourages molecular-level control over key redox transitions involving small-molecule substrates (O2, and H2O), at or near electrode surfaces. While many molecular catalysts have been shown highly active for OER, immobilizing those onto the heterogenous solid matrices is challenging. Herein, graphene quantum dots (GQDs), a carbonaceous sub-class, was used as the solid matrices to conjugate the molecular catalyst onto its surface owing to its high surface area and electronic conductivity. Through the coordinated environment of the conjugated material, the molecular Fe sites on the GQDs surface exhibited outstanding OER features, achieving an ultra-low overpotential of 223 mV and 241 mV at a current density of 50 and 100 and mA/cm2, respectively, and excellent stability over 24 h. Our results marked a pioneering step in that through conjugation, these molecular sites were well dispersed at the GQDs matrices and were intrinsically active for OER.